Effectiveness of Catching Free Radicals in Cigarette Smoke with Biofilters Made from Bidara Leaf Powder - Mulyono, Agus; sasmitaninghidayah, wiwis (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2021)
A number of diseases have been stigmatized as a side effect of smoking and its smoke. Reducing the dangers of smoking by capturing radioactive substances from cigarette smoke is one way to reduce or reduce the level of danger. This study aims to make a filter made from bidara leaf powder to bind free radicals in cigarette smoke. Bidara leaf powder with PEG solution was mixed and stirred until homogeneous with variations in the mass of bidara powder 0.7 grams, 0.8 grams, 0.8 grams, 0.9 grams and 1 gram. The product was molded with a 0.7 cm diameter pipe hose, allowed to dry before being removed from the mold, and heated at a temperature of 105o C for 20 minutes. Biofilter matrix using polyethylene glycol (PEG) and egg white, bidara leaf powder as a biofilter filler. The physical characteristics of the membrane were obtained by conducting density and porosity tests with SEM. The effectiveness of the biofilter membrane is known by passing cigarette smoke, then the number of free radicals trapped in the biofilter is analyzed using ESR. The results showed that the use of a biofilter made from bidara leaf powder with a mass of 0.9 grams with an egg white matrix was able to bind 85.7% of free radicals (C, O2-, C, Peroxy, CO2-, and Hydroperoxides) with 100% effectiveness, density. 0.893 g/cm3 and porosity 0.6788%. Testing the characteristics of the biofilter with SEM (Scanning Electron Microscopy) shows the size of the biofilter pores between 2-3 m, while the size of free radicals in cigarette smoke ranges from 20-430 nm. This indicates that the ability to bind free radicals in cigarette smoke is influenced by the antioxidant activity of bidara leaf powder (filler biofilter).